Phenotypic variability confirmed by nuclear ribosomal DNA suggests a possible natural hybrid zone of Triatoma brasiliensis species complex - Costa, Jane; Bargues, Maria Dolores; Neiva, Vanessa Lima; Lawrence, Gena G.; Gumiel, Marcia; Oliveira, Genova; Cabello, Pedro; Lima, Marli Maria; Dotson, Ellen; Provance, David William; Almeida, Carlos Eduardo [UNESP]; Mateo, Lucia; et al. (Elsevier B.V., 2016)
Triatoma brasiliensis macromelasoma occurs in Pernambuco state, Brazil, which is situated between the distribution areas of Triatoma brasiliensis brasiliensis (north) and Triatoma juazeirensis (south). T. b. macromelasoma displays greater variations in its chromatic phenotype than either T. b. brasiliensis or T. juazeirensis, and patterns reminiscent of one or the other. Experimental crosses from each of these members of the T. brasiliensis species complex generated fertile offspring suggesting that viable hybrids could be present in nature, despite their significant genetic distances. Considering the geographical position of occurrence of the T. b. macromelasoma (in Pernambuco) it was proposed to be an area capable of supporting natural hybridization between T. b. brasiliensis and T. juazeirensis. Since phenotypic variability is expected, this study investigated the existence of intermediate chromatic phenotypes for T. b. macromelasoma in various locations in areas between the T. b. brasiliensis and T. juazeirensis occurrences. Thirteen different color patterns were for the first time characterized and nine of those displayed intermediate phenotypes. Molecular analysis performed using ribosomal DNA intergenic region, grouped all within the T. brasiliensis complex. The intermediate chromatic phenotypes, molecular analysis and experimental crosses all support the distinction of a zone of hybridization that gave rise to the T. b. macromelasoma through homoploidal evolution. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Triatominae; Phenotype; Speciation; Hybridization; Epigenetics